A community participatory intervention model to reduce the health risks from biogas wastewater in Hanam Province, Vietnam - Luu Quoc Toan; Nguyen Mai Huong; Nguyen Tien Thanh; Pham Thi Huong Giang; Hanh Tran-Thi-Tuyet; Tran Minh Hang; Dinh Xuan Tung; Phuc Pham Duc; Hung Nguyen-Viet (Hanoi School of Public Health, 2016)
In Vietnam, using biogas to treat livestock waste is common, in particular on small holder farms. However, most small holder farms do not know how to use biogas correctly and wastewater can affect health and the environment. Using a participatory approach with farmers and other stakeholders we developed and implemented a set of interventions in Hanam province to reduce health risks from biogas wastewater. Twenty-four pig farmers were selected as a "core group" to be instrumental in developing the interventions and training other farmers to correctly use biogas. The intervention model was piloted for 6 months. Several outputs were obtained including i) approval and enforcement of a "huong uoc - village law" on environmental protection; ii) training of 24 farmers from the core group in communication skills to share information on using biogas; iii) development of a 6-step program of pig cage cleaning to limit waste loaded to biogas to improve the efficiency of biogas production; iv) a health monitoring books for humans and animals for use by families in the community. The results provided evidence that applying the participatory approach can lead to improved knowledge and practices of farmer using biogas and can reduce the health risks from biogas wastewater.